Histological Differences of the Vascular Wall Between Sites With High and Low Prevalence of Intracranial Aneurysm. Issue 7 (6th May 2019) - Laarman, Melanie D; Ruigrok, Ynte M; Nierstrasz, Renske C S; Spliet, Wim G M; Van Hecke, Wim; Algra, Ale; Rinkel, Gabriël J E
Abstract: Intracranial aneurysms (IAs) develop more often on bifurcations compared with the rest of the circle of Willis (CoW). We investigated histological differences between 2 high IA prevalence sites (anterior communicating artery [AcomA] and basilar tip) and 2 corresponding low IA prevalence sites (anterior cerebral artery [ACA] and basilar artery [BA]) using histological sections of 10 CoWs without IAs. Medial defect density in the AcomA was 0.24 medial defects/mm compared with 0.02 for the A1 part and 0.03 for the A2 part of the ACA. In the basilar tip we found 0.15 medial defects/mm compared with 0.14 in the BA. Vascular smooth muscle cells (VSMCs) were more often disorganized in both high-prevalence sites (AcomA: 10/10, basilar tip: 5/10) compared with low-prevalence sites (both ACA and BA: 1/10). Intima thickening was more severe in the high-prevalence sites. Vascular wall thickness was not significantly different between high- and low-prevalence sites, but had a larger variance in high- compared with low-prevalence sites (AcomA vs ACA: p = 6.8E–12, basilar tip vs BA: p = 0.02). Disorganized VSMCs at high-prevalence sites likely result in a higher susceptibility to hemodynamic stress, leading to more vascular remodeling (such as intima thickening), which could increase the likelihood of IA formation.